NULL HEADS AND DP-INTERNAL CONCORD IN BARI (The University of Nairobi Journal of Language and Linguistics, 2023)
This paper provides evidence from Bari, an Eastern Nilotic language found inthe southern Sudan, that not all that are known as ‘Determiners’ aregenerated in the D-head of DP as has been advocated by Abney (1987) andothers. In agreement with Guisti (1992); Guisti and Giuliana (1994) andSzablocsi (1987), the paper argues that ‘determiners’ do not constitute onehomogeneous categorial and structural group. It shows that co-occurrenceof determiners in DP is due to the fact that these elements are generated indifferent positions and therefore target different positions within DP. Itclaims that that is the case because DP, at least in Bari, contains Xmaxintermediate projections between D and the complement of NP which hoststhe determiners. These intermediate Xmax projections are obligatorilyselected each time the modified head N selects a modifier. The paperfurther claims that the heads of these projections, including the D-head ofDP, are null and that the so-called determiners and other modifiers such asadjectives are base-generated in Spec-positions in DP and other embeddedcomplement projections within DP. These null heads are targets of Nmovement of the modified head noun which rises head-to-head, triggeringwidespread Spec-Head agreement within DP and other complementprojections embedded in DP. Since the determiners are generated in Specprojections, this Spec-head relation, the paper argues, accounts for why amodifying determiner or adjective agrees in number and gender with thehead noun it modifies.